Mengenal HIV/AIDS Sedini Mungkin guna Mencegah Terjadinya Penularan pada SMA Bawakaraeng - Ricky. Z; Rusli Abdullah; Abd. Herman Syah Thalib; Sakina Latabila; Sela Djama (Universitas Muhammadiyah Manado, 2021)
The lack of appropriate and relevant information about HIV/AIDS, and supported by the curious attitude of teenagers, causes them to become one of the populations with high-risk behavior. Prevention of HIV/AIDS needs to be maintained by teenagers or high school students so that it does not have a comprehensive impact on the health of teenagers, which of course is detrimental to the current generation. The solution that can be done is the delivery of material (education) and how to prevent HIV/AIDS for teenagers so that they do not contract this deadly disease. The form of this activity is in the form of health education from a team of nursing lecturers assisted by students with participants, namely high school teenagers who are participants in this activity as many as 44 students. During the implementation of the activity, don't forget to give quizzes and ways to prevent HIV/AIDS and everything related to HIV disease. /AIDS as part of the goal of mastering the material from participants in this PKM activity. Apart from that, an evaluation of the extent of mastery and benefits of this activity is carried out.